Influence of small amounts of Si and Cr on the high temperature oxidation behavior of novel cobalt base superalloys. (15th May 2021) - Liang, Zhida; Göken, Mathias; Lorenz, Uwe; Neumeier, Steffen; Oehring, Michael; Pyczak, Florian; Stark, Andreas; Wang, Li
Highlights: The effect of small amounts of Si on oxidation resistance in Co-base superalloys is better than that of Cr. The formation of a continuous Al2 O3 scale can be induced by minor amounts of Si but not Cr. Alloying Cr or Si can improve the adhesion between oxide layers and metal substrates and inhibit spallation of oxide layers. Abstract: The effect of small amounts of Si and Cr on the high temperature oxidation of alloys based on Co-9Al-9W was investigated at 900 °C. The results show that the effect of Si additions on oxidation resistance was more pronounced than for Cr additions. An addition of 4 at.% Cr was insufficient to produce a protective layer, while 2 at.% Si led to the formation of a dense, continuous Al2 O3 scale. The thermodynamics and kinetics for Al2 O3 layer formation were analyzed by combining CALPHAD and Wagnerʼs theory.